Exploring English Language Acquisition in A 4-Year-Old Makassaresse Child: A Case Study - Nurwanti Nurwanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research examines the acquisition of English by a 4-year-old Makassarese child. From the moment of her birth, the child has been exposed to the Makassarese and Indonesian languages. Presently, the child is currently acquiring English as a third language. The present research employed a qualitative case study method, incorporating observation, recording, and interviews with parents. The findings indicate that the child has acquired basic vocabulary and English sentence structures sufficient for daily interaction. The phenomenon of code-switching among English, Indonesian, and Makassarese languages is a recurrent theme, particularly during play, which illustrates how the child naturally and strategically uses her multilingual skills. The findings indicate that digital media, interaction with English-speaking peers, and consistent parental support are pivotal factors in the language acquisition process. Despite their interaction with a foreign language, children maintain their cultural identity through the incorporation of typical Makassarese elements into their daily conversations. This research underscores the significance of early exposure to multiple languages and the role of a nurturing socio-cultural and environmental context in facilitating children's language development.